Penyadapan Pada Internet Melalui Website Camera Sebagai Sarana Pembuktian Dalam Penegakan Hukum Terhadap Kasus Prostitusi On Line - Antonius Sudirman; Nitha Vandeuw (Jurnal Pemberdayaan Hukum, 2011)
This study examines the problems, the effectiveness of wiretapping (interception) on the internet using a web camera in the law enforcement of prostitution on line via video-converence. The aim of which is to gain the analysis of the effectiveness of wiretapping of the internet using web  camera in the law enforcement of online prostitution case trough a video conference on 17 years of age or older. For the purpose, data collection is done through the study of documents and interviews with makassar Polwiltabes (Regional Police Office) investigators and the cam frog user. ............